2007
DOI: 10.1063/1.2743420
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of molecular hydrogen and hydrogen sulfide on Au clusters

Abstract: The authors present theoretical results describing the adsorption of H2 and H2S molecules on small neutral and cationic gold clusters (Aun(0∕+), n=1–8) using density functional theory with the generalized gradient approximation. Lowest energy structures of the gold clusters along with their isomers are considered in the optimization process for molecular adsorption. The adsorption energies of H2S molecule on the cationic clusters are generally greater than those on the corresponding neutral clusters. These are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
4
36
1
1
Order By: Relevance
“…2 it can be observed that in all cases, the two H atoms prefer binding to the same metal atom and form H-H-M triangular geometry. Similar phenomenon has been also observed in H 2 molecular adsorption on small neutral and cationic Au n clusters [1][2][3]. In tetramers and pentamers the H atoms like to bond with the three-coordinated metal site, that is, H 2 prefers locating at the short diagonal of the rhombic tetramers and the upper bottom of the trapezoidal pentamers.…”
Section: Structures and Stabilitiessupporting
confidence: 55%
See 2 more Smart Citations
“…2 it can be observed that in all cases, the two H atoms prefer binding to the same metal atom and form H-H-M triangular geometry. Similar phenomenon has been also observed in H 2 molecular adsorption on small neutral and cationic Au n clusters [1][2][3]. In tetramers and pentamers the H atoms like to bond with the three-coordinated metal site, that is, H 2 prefers locating at the short diagonal of the rhombic tetramers and the upper bottom of the trapezoidal pentamers.…”
Section: Structures and Stabilitiessupporting
confidence: 55%
“…The phenomenon that H 2 dissociation was not observed experimentally is not due to the higher dissociation barrier and weak binding of H 2 . Kshirsagar et al investigated the adsorption of H 2 molecules on small neutral and cationic Au n clusters up to eight Au atoms [2]. They found that H 2 molecule weakly binds to the neutral Au n clusters as compared to the corresponding cationic Au n ?…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In 1978, Hay et al [49] performed the ab initio studies on diatomic gold hydride using relativistic effective core potentials. Later, a number of experimental and theoretical studies have been reported about the interaction of the gold clusters with hydrogen [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. In 2003, the photoelectron spectra of bare Au n À and Au n-1 H À clusters were presented by Buckart et al [68], and the spectra of Au n À and Au n-1 H À clusters showed almost identical features for n > 2 suggesting that hydrogen behaved as a protonated species by contributing one electron to the valence pool of the Au n À cluster.…”
Section: Introductionmentioning
confidence: 99%
“…This has been investigated in some previous works for H 2 , NO, CO and H 2 O adsorption onto small Au clusters [41][42][43]. It can be seen from Figure 2 that for both end-on and bridge adsorption modes, the adsorption energies of O 2 on odd-numbered Au n clusters are larger than those on adjacent even-numbered ones.…”
Section: O 2 Adsorption Energiesmentioning
confidence: 85%